2014 International Conference on Unmanned Aircraft Systems (ICUAS) 2014
DOI: 10.1109/icuas.2014.6842296
|View full text |Cite
|
Sign up to set email alerts
|

The design and construction of a high endurance hexacopter suited for narrow corridors

Abstract: We have conceived a novel compound multicopter (helicopter type utilizing multiple different size propellers for separate lift and attitude control) configuration specifically for flight through narrow corridors. Its design combines the contradictory requirements of limited width, high agility and long endurance while carrying a significant payload. This *Research supported by Kulab (Propolis) and KULeuven (FWO-project 6.0404.10).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 7 publications
(6 reference statements)
0
25
0
1
Order By: Relevance
“…UAV and related technologies are developing quickly with more and more efficiency and currently, the main limitation of UAV multirotor is energy (batteries). However, as the following papers show [57,58], these problems are being addressed by several research groups. Our research does not depend on the crop field size.…”
Section: Effect Of Uav Flights Parameters On Orthophoto Spatial Resolmentioning
confidence: 99%
“…UAV and related technologies are developing quickly with more and more efficiency and currently, the main limitation of UAV multirotor is energy (batteries). However, as the following papers show [57,58], these problems are being addressed by several research groups. Our research does not depend on the crop field size.…”
Section: Effect Of Uav Flights Parameters On Orthophoto Spatial Resolmentioning
confidence: 99%
“…There is a representative study on new types of multicopter such as Dual Quad-Rotor System, Compound Hexa-copter, Variable-Pitch Gasoline-Engine Quad rotor [5][5] [6]. There are also studies on Tether powered multicopter [6]. The results of the study are shown in Figure 1 below.…”
Section: Introductionmentioning
confidence: 88%
“…However, the outcome, performance and basic mission functions gained by active research have a limited effect by the short flight time of existing multicopters [5,6]. As shown above, research is also actively being carried out to improve the flying time which is pointed out as the biggest disadvantage of multicopter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Their specifications are given in Table 1. These two vehicles were chosen for their difference in configuration, weight, inertia, and moment arms between propellers.…”
Section: à ámentioning
confidence: 99%